Change of Beauty Standards in Indonesian Society Through Beauty Product That Improve Lately - Saraharah, Zona Dyota; Ningtyas, Sulistya (Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
Beauty products that continue to use the words whitening or brightening when selling their products to Indonesians even though most Indonesians have a variety of colors, not just white or bright. This research aims to explore people's views regarding beauty standards which are now starting to change in people's views, reflected in local beauty products promoted by brands that continue to improvise. The method used in the research is a constructive paradigm by interviewing several participants. The results of this research are the opening of the view that beauty cannot be made or set to a standard, especially as many local beauty products make products to suit Indonesian people's skin color. Awareness and openness of people's minds, especially young people, who know that social media is a means to be open to the uniqueness of each individual's beauty.